2011
DOI: 10.1088/1742-6596/294/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Polarized3He cell development and application at NIST

Abstract: Over a period of well over a decade, a large number and variety of polarized 3 He cells for neutron applications have been developed and tested at the U.S. National Institute of Standards and Technology (NIST). These cells have primarily been employed for spinexchange optical pumping (SEOP), and applied to neutron scattering and fundamental neutron physics. We describe the procedures we have employed for producing these cells, as well as their characteristics and applications. Whereas our best results are for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 70 publications
0
46
0
Order By: Relevance
“…Data were collected in both a − a (basal) plane and a−c plane geometries. Polarized neutron scattering measurements were performed using a 3 He-based apparatus 33 with open -50' -80' -120' collimation, a vertical guide field, and 14.7 meV final energy. A flipping ratio of 60 was determined from the nuclear (2, 0, 0) reflection.…”
Section: A Experimentsmentioning
confidence: 99%
“…Data were collected in both a − a (basal) plane and a−c plane geometries. Polarized neutron scattering measurements were performed using a 3 He-based apparatus 33 with open -50' -80' -120' collimation, a vertical guide field, and 14.7 meV final energy. A flipping ratio of 60 was determined from the nuclear (2, 0, 0) reflection.…”
Section: A Experimentsmentioning
confidence: 99%
“…Presence of such unpolarized helium atoms would limit the attainable 3 He polarization. Actually, the vitreous silica cells, which have large microscopic holes, have lower attainable 3 He polarization [22][23][24]. In the present study, it was found that blown GE180 glass has more disordered structure.…”
Section: Pair Distribution Functionsmentioning
confidence: 45%
“…The 3 He cell (Mars) was fabricated at NIST using the procedure outlined in [29]. The cell body is made from Corning 1720 with optically flat windows made from reblown GE180 alumina silicate glass.…”
Section: He Analysermentioning
confidence: 99%
“…The windows are 8 mm thick and the cell body is 80 mm long with an inner diameter of 60 mm. The cell pressure measured by neutron transmission at NIST is 0.9 Bar [29,30]. The flat windows provide a uniform analysing path for the scattered beam because they provide for a uniform path length through the cell, compared to reblown cells.…”
Section: He Analysermentioning
confidence: 99%